2014
DOI: 10.13080/z-a.2014.101.048
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of grain yield and its components in spring triticale under different N fertilization regimes

Abstract: Grain yield is a result of an organized interplay of several yield components, which are highly susceptible to environmental fluctuations. However, there is still a lack of knowledge about the relationship between grain yield and factors governing it. Experiments were conducted during the period 2008-2011 at the Institute of Agriculture, Lithuanian Research Centre for Agriculture and Forestry in Central Lithuania (55023′50″ N and 23051′40″ E) on an Endocalcari-Endohypogleyic Cambisol (CMg-n-w-can). The correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 14 publications
3
14
0
1
Order By: Relevance
“…In a study by Alaru et al [33], the strongest effect on the yield volume and structure was produced by the years of the experiment, followed by the cultivar and then the division of the nitrogen fertilization dose. This supports the earlier studies conducted by other authors, who reported that the yield volume and quality of triticale depended not only on fertilization but also on the weather conditions [34,35]. Biberdžić et al [12] mention the weather as one of the most important factors affecting the yield of grain.…”
Section: Grain Yieldsupporting
confidence: 88%
“…In a study by Alaru et al [33], the strongest effect on the yield volume and structure was produced by the years of the experiment, followed by the cultivar and then the division of the nitrogen fertilization dose. This supports the earlier studies conducted by other authors, who reported that the yield volume and quality of triticale depended not only on fertilization but also on the weather conditions [34,35]. Biberdžić et al [12] mention the weather as one of the most important factors affecting the yield of grain.…”
Section: Grain Yieldsupporting
confidence: 88%
“…According to Obuchowski, et al [48], the starch content in grain is an important, but not solitary factor used to assess the suitability of triticale for bioethanol production. Another significant consideration is the grain yield per cropped field unit [48,49], which largely depends on the weather conditions and the dose of mineral nitrogen fertilization [50,51]. Therefore, despite a significantly lower content of starch in grain, the high-input production system supplied bioethanol yield per unit of the cropped fields higher by 25.0% than the low-input production system.…”
Section: Low-inputmentioning
confidence: 99%
“…The yield of grain, starch, and bioethanol in triticale cultivation is highly variable and highly dependent on weather conditions during the growing season. This variability may be particularly limited by appropriate crop management, especially mineral fertilization [49,50]. Thiemt and Oettler [53] claim that the high genetic variability of grain traits affecting the yield of ethanol that occurs within elite triticale breeding material, implicating high potential for breeding and selecting triticale toward higher ethanol productivity.…”
Section: Low-inputmentioning
confidence: 99%
“…However, grains of lower quality, not suitable for consumption or animal feed production, can be used for energy purposes. In addition, grains affected by fungal diseases can be used for energy generation purposes [27].…”
Section: Introductionmentioning
confidence: 99%